2013
DOI: 10.1002/stem.1364
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Mesenchymal Stem Cells Promotes Tissue Regeneration in a Glaucoma Model Through Laser-Induced Paracrine Factor Secretion and Progenitor Cell Recruitment

Abstract: Among bone marrow cells, hematopoietic and mesenchymal components can contribute to repair damaged organs. Such cells are usually used in acute diseases but few options are available for the treatment of chronic disorders. In this study, we have used a laser-induced model of open angle glaucoma (OAG) to evaluate the potential of bone marrow cell populations and the mechanisms involved in tissue repair. In addition, we investigated laser-induced tissue remodeling as a method of targeting effector cells into dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 64 publications
7
95
1
4
Order By: Relevance
“…53,54 Bone marrow-derived mesenchymal stem cells are multipotent and have been explored for TM regeneration. 55 In the study by Manuguerra-Gagne et al, 55 MSCs were injected into the anterior chamber of rats with laser-induced glaucoma. MSC injection induced a rapid return to normal IOP levels in experimental glaucomatous rats.…”
Section: Other Stem Cell Sources For Tm Regenerationmentioning
confidence: 99%
“…53,54 Bone marrow-derived mesenchymal stem cells are multipotent and have been explored for TM regeneration. 55 In the study by Manuguerra-Gagne et al, 55 MSCs were injected into the anterior chamber of rats with laser-induced glaucoma. MSC injection induced a rapid return to normal IOP levels in experimental glaucomatous rats.…”
Section: Other Stem Cell Sources For Tm Regenerationmentioning
confidence: 99%
“…Manuscripts covered many advances in understanding the fundamental mechanisms that control stem and progenitor cell fate, and advances in working toward treating all tissues, from the lower extremities to the brain. Exciting basic and translational research was reported in using stem cells to treat osteoporosis [11], spinal cord injuries [12,13], radiation-induced fibrosis [14], glaucoma [15], globoid cell leukodystrophy [16], stroke [17], and Huntington's disease [18], to name just a few. It has truly been an exciting year, as we watch the stem cell field explode.…”
mentioning
confidence: 99%
“…This can be shown to be the case with photoreceptor transplants, 13 but may not be the case for other stem cells delivered to other sites in the body, with a paracrine mode of action favoured for some. [26][27][28] In this case, the premise is that secretion of hormones, growth factors and/or extracellular matrix components by the stem cells, in complex dialogue with pre-existing damaged tissue, may be stimulating transplanted cells to secrete therapeutic substances in response to the injured host tissue, thereby providing benefit. [26][27][28] The addition of pRPCs with glial potential to damaged retinas may enhance natural repair processes, by physical contact and structural repair, by providing an antiapoptotic effect (as suggested by increased Bcl2 levels), and by secretion of hormones and/or growth factors [26][27][28] or, perhaps, via increased glial protection of normally unmyelinated segments of ganglion cell axons.…”
Section: Molecular Markersmentioning
confidence: 99%